Development of a Reliable Information System for Medical Device Inventory in Hospitals: A Systematic Literature Review - Suryati (HM Publisher, 2023)
Developing an information system for medical equipment inventory in hospitals not only includes technical aspects but also involves an in-depth understanding of the operational needs of the hospital itself. By utilizing the latest technology, such as the Internet of Things (IoT), and efficient data integration, hospitals can ensure that the information systems developed can adapt to the dynamics of future technological needs and developments. This study aimed to explore the development of a reliable information system for inventory of medical equipment in hospitals. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the development of a reliable information system for the inventory of medical devices in hospitals. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Developing an information system for medical device inventory in hospitals is a crucial step in improving the efficiency, availability, and management of health resources. Developing an information system for medical device inventory in hospitals is not just about recording and monitoring but also providing a holistic solution to improve operational efficiency and patient service.